IJCH – COVID-19 in the Arctic: special issue - Gwen Healey Akearok (International Journal of Circumpolar Health)
The Circumpolar region, comprising the Arctic territories encircling the North Pole, is home to diverse Indigenous cultures facing unique socio-economic challenges. Indigenous communities such as the Inuit, Sámi, Athabaskan, Gwitchin, and Russian Arctic groups exhibit rich traditions and adaptive practices tied to their environments. Environmental diversity, from icy tundra to boreal forests, influences livelihoods and biodiversity, while significant socio-economic disparities persist, impacting access to healthcare, education, and economic opportunities. Against this backdrop, the global COVID-19 pandemic accentuated the intersection of environment, culture, and health in remote Arctic regions, presenting distinct challenges and opportunities. Initiated by a collaborative research project led by Fulbright Arctic Initiative Alumni, this special issue of the International Journal of Circumpolar Health explores the impacts of COVID-19 on Arctic Indigenous and rural communities. Building on previous work and recommendations, the issue features community case studies, highlighting community experiences and collaborative approaches to understand and address the pandemic’s effects. The authors highlight both positive and negative societal outcomes, presenting community-driven models and evidence-based practices to inform pan-Arctic collaboration and decision-making in public health emergencies. Through sharing these insights, the special issue aims to privilege local and Indigenous knowledge systems, elevates community responses to complex and multifaceted challenges, and contributes to the evidence base on global pandemic response.